PEDAGOGIK DAN BUDAYA POSITIF UPAYA MEMBENTUK KARAKTER SISWA HOLISTIK - Uyun, Hairul; Babang Robandi; Ni Made Winursiti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research explores the central role of pedagogy in forming a positive culture in the school environment. Through an in-depth review of related literature and real case studies, this research reveals that implementing a student-focused learning approach, combined with instilling positive values ​​and inclusive practices, is able to create a learning ecosystem that supports students' holistic growth. Research data proves that a positive school culture not only contributes to increasing academic achievement, but also forms students' strong, independent and empathetic character. Furthermore, this research analyzes several aspects that influence the success of positive culture implementation, such as visionary leadership, involvement of all stakeholders, and ongoing support. The results can add insight into important implications for educators, regulators and the entire school community in efforts to create an optimal learning environment for the younger generation.